Enhancing productivity of rice-fallows of eastern India through inclusion of pulses and oilseeds - Kumar, Rakesh; Mishra, J. S.; Hans, Hansraj (Indian Farming, 2018)
Rice fallows thus offer a great opportunity to maximize the area of pulses with adoption of advance agro-techniques. Soil-moisture conservation and mitigation of abiotic stresses is two successful trapping of rice fallows. Locationspecific,short duration, droughtresistant varieties of pulses are vital for rice fallows area. Further, extension system needs to be strengthened to sensitize the farming community. This way, pulses and oilseeds can be included as an integral part of rice-fallow production system. Among technical constraints, low residual soil moisture coupled with lack of irrigation, poor soil and crop management are important, whereas among socio-economic constraints, labour shortage, poor economic status of farmers, poor extension services, lack of availability of inputs and fragmented land size are important.